An Exploratory Study on Farmer’s Perception about dairy-based Farmer Producer Companies in India - KUMAR, SUNIL; SANKHALA, GOPAL; KAR, PRIYAJOY; SHARMA, P H ROMEN; KUMAR MEENA, DEVENDRA (The Indian Journal of Agricultural Sciences, 2022)
Farmer Producer Company (FPCs) has emerged as a novel collective approach model and is considered to be a very effective tool for improving the overall socio-economic development of small and marginal farmers in India. To authenticate this prerogative, a survey was conducted among 360 dairy farmer members of 12 dairy-based farmer producer companies in three states of India. Most of the farmers expressed that the major objectives of FPCs are to maximize the benefits of members (75.50%), capacity building of its members (76.38%), better accessibility of agricultural services (74.44%) followed by reducing the transport cost of members (72.75%). Furthermore, the study has also investigated the socio-economic variables and their relationship with the individual perception of the farmer about FPCs. Findings aid us to formulate an appropriate strategy that will help to improve the farmers’ perception about the FPCs. Enhanced farmers’ awareness and knowledge about the beneficial effects of FPCs will encourage fellow farmers to form FPCs and reap its benefits on a larger scale